IMPLEMENTATION OF VILLAGE FINANCIAL SYSTEM AND ITS EFFECT ON QUALITY OF FINANCIAL STATEMENTS IN JEMBER DISTRICT - Enita Lestine Aurriel A; Agustin HP; Nurshadrina Kartika Sari (STIE Mandala Jember, 2020)
This research was carried out on the basis of Law No. 6 of 2014 concerning villages, andbased on an appeal letter from the Ministry of Home Affairs and KPK, in 2017 Siskeudeswere introduced in 28 Sub-Districts and 226 Villages in Jember Regency, Semboro District.The population is in the research of the village government officials in Semboro District. Thisresearch used test for testing instruments, classical assumption tests and hypotheses testing.What is obtained is the driver's performance of linear regression analysis betweenindependent variables and dependent variables simultaneously or simultaneously. The resultsshowed the application of Siskeudes, competency of human resources, understanding ofaccounting, education and training, village assistance simultaneously had an effect on thequality of financial statements of 44.2%. While the independent variables with independentvariables show that the application of siskeudes, education and training, village assistancedoes not affect the quality of financial statements. Accounting understanding has a negativeeffect on the quality of financial statements. Human resources competencies negatively affectthe quality of financial statements.